A study on health consciousness among the elderly in a rural population of Katihar, Bihar - Soni, Sneha; Kumar, Manish; Shukla, Mukesh (International Journal of Scientific Reports, 2016)
Background: India is passing through a major demographic and epidemiological transition there by leading to increasing geriatric problems as burning public health issue within the nation. The present cross-sectional study was undertaken to study health consciousness among the elderly in a rural population of Katihar. Methods: The present study was conducted in rural field practice area of Katihar medical college and a total 450 elderly persons were interviewed using pre-designed, pre-tested semi structured questionnaire regarding their health consciousness and health seeking behavior during the study period of one year, from Jan 2013 to Dec 2013. Data was entered in Microsoft excel and analyzed by using frequency and proportion. Results: Majority (69.7%) of the elderly were conscious about health, followed by reluctant group (16.6%), while 13.5% were not conscious about their health. Factors like gender (p=0.00), marital status (p=0.02), social category (p=0.00), educational status (p=0.00), occupation (p=0.00) and financial dependency (p=0.04) were found to be significantly associated with health consciousness among elderly. Conclusions: On the basis of these findings, it can be recommended that there is a need not only to develop comprehensive geriatric health-care services, but community based intervention are also needed to increase the overall knowledge and consciousness towards health so as to improve their health seeking behaviour.